Hepatoid Adenocarcinoma of the Stomach: Current Perspectives and New Developments - Xia, Ruolan; Zhou, Yuwen; Wang, Yuqing; Yuan, Jiaming; Ma, Xuelei (Frontiers in Oncology, 2021)
Hepatoid adenocarcinoma of the stomach (HAS) constitutes uncommon malignancies accounting for only 0.17-15% of gastric cancers. Patients are often diagnosed at an advanced disease stage, and their symptoms are similar to conventional gastric cancer (CGC) without specific clinical manifestation. Morphologically, HAC has identical morphology and immunophenotype compared to hepatocellular carcinoma (HCC). This is considered to be an underestimation in diagnosis due to its rare incidence, and no consensus is reached regarding therapy. HAS generally presents with more aggressive behavior and worse prognosis than CGC. The present review summarizes the current literature and relevant knowledge to elaborate on the epidemic, potential mechanisms, clinical manifestations, diagnosis, management, and prognosis to help clinicians accurately diagnose and treat this malignant tumor.